Strategic Approaches to Enhancing Financial Performance: Financial Literacy and Social Capital as Pillars of Business Resilience Amid Global Economic Challenges - Yuliusman Yuliusman; Wirmie Eka Putra; Fredy Olimsar; Nyimas Dian Maisyarah; Dahmiri Dahmiri (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the effect of financial literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs), with social capital serving as a mediating variable in Jambi City, Indonesia. This research employs a mixed-methods approach, combining quantitative analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with qualitative insights from in-depth field interviews. The study sample comprises 395 MSME owners selected using Slovin's formula. The results reveal that financial literacy has a positive and significant effect on both financial performance and social capital. Furthermore, social capital significantly influences financial performance and mediates the relationship between financial literacy and MSME financial performance. These findings highlight that financial literacy is not merely a technical capability in managing finance but also a strategic competence in building trust, networks, and social collaboration that enhance business competitiveness. The novelty of this research lies in integrating cognitive and social dimensions into a single empirical model to explain MSME financial resilience. Practically, the findings provide strategic insights for policymakers and practitioners to design empowerment programs that enhance financial literacy and strengthen social capital, thereby improving MSME performance and sustainability amid global economic dynamics.